Biodiversity and evolution - Grandcolas, Philippe; Maurel, Marie-Christine (ISTE Press Ltd ; Elsevier Ltd, 2018)
Biodiversity and Evolution includes chapters devoted to the evolution and biodiversity of organisms at the molecular level, based on the study of natural collections from the Museum of Natural History. The book starts with an epistemological and historical introduction and ends with a critical overview of the Anthropocene epoch.